Palavras e imagens : da oralidade ao hipertexto - Paim, Madalena Teixeira (2008)
The present study investigates the relationship between the oral or written words with the images, based on theoretical studies and on some literature productions analysis. In the first moment, when the oral word is the only form to preserve the knowledge, the images are projected in the human mind. It is not necessary to have them in another support, because all the community members share the same experiences. Following this period, in the second one, the handwritten or printed words sometimes demand for images, since the books are not linked just to one community. They even can be from another period of time and images can be very helpful. Later, but still in the same period, they are used to improve the presentation of the printed books and, in this way, it was created a new style for them. Finally, when technology brings some new ways of presenting the literature creations, the words remain as a kind of link between them and the images while these ones can build the story by themselves